EFFECT OF SKILL APPROACH TO PROCESS OF STUDENT LEARNING SMA NEGERI 1 SEUNUDDON NORTH ACEH - Irwan Susanto (Universitas Negeri Medan, 2015)
This study aims to determine the skills approach to the learning outcomes of students in the subject matter of heat in class X at SMA Negeri 1 Seunuddon Aceh Utara. This research is a form of experiment. The population in this study were all second semester class X at SMA Negeri 1 Seunuddon Aceh Utara T.P.2013/2014 consisting of two classes of 60 people. The sample of this study is the total sample is X-1 (class experiment) is taught with the skills approach, and X-2 (control group) were taught using the conventional approach amounted to 30 0rang. Research instrument is the achievement test in the form of 20 multiple-choice questions that consists of 5 options first tested on students outside of the sample, to determine the validity, reliability, distinguishing features, and level of difficulty of the test. From the results of this study showed the average value of the experimental class pretest was 41.66 and 38.66 the control class is through testing prior knowledge obtained t <t table (1.511 <2.002) These results indicate that the ability of the two classesare the same initial. Then given a different treatment. Experimental class withthe skills approach and control classes with conventional approaches. Aftertreatment carried posttest with an average yield of 73.00 experimental class and control class 60.66. From the results of the t test obtained t> t table (4.224>1.671) with α = 0.05 df = 58, it can be concluded that there is a significant influence on the process skills approach to student learning outcomes in the subject matter of heat in class X at SMA Negeri 1 Seunuddon Aceh UtaraT.P.2013/2014.